Internal control system as means of fraud control in deposit taking financial institutions in Imenti North Sub-County - Nyakarimi, Samuel N.; Karwirwa, Mary (IISTE, 2015)
The purpose of the study was to establish the relationship between internal control systems (ICS) and fraud control in deposit taking financial institutions. ICS was analyzed based on its component which include; Control Environment, Risk Assessment, Control Activities, Information and Communication and Monitoring. The Researcher set out to establish how ICS could be used to control fraud in financial institutions. The researcher set study objectives and hypotheses that assisted in establishing the relationship sort. The research was conducted using both quantitative and qualitative approaches using Stratified random sampling, ANOVA and Descriptive Research Designs. Data was collected using Questionnaires from the operations managers and supervisors, from various deposit taking financial institutions in Imenti North Subcounty. A sample of 92 respondents from a population of 120 was used for this study. Data was analyzed using the Statistical Package for Social Scientists (SPSS) where conclusions were drawn from tables and figures derived from the Package. The study found that the financial institutions analyzed recruit through vetting on competences and integrity, the organization structure reflects chain of command, there are proper follow-up of delegated responsibilities and the employees are promoted and compensated fairly. On risk assessment the study revealed that the institutions have proper mechanisms of mitigating risks, financial documents are properly kept, and there are processes of identifying and estimating risks. Though there was agreement that there are no cases of missing documents to authenticate transaction the analysis reflected a low mean than in other parameters. In analyzing control activities it was found that transactions are undertaken by authorized personnel, reconciliations are done regularly, proper accounting principles are applied and there is proper segregation of duties. Further the study showed that there is job rotation and verifications are done to reduce chances of forgery. The study revealed that the institutions have developed means of passing information, the employees are informed of their roles, besides engaging external parties to verify financial statements they also act upon the findings quickly. In monitoring organizations have evaluation mechanisms, they also have plans on activities and ensures that the laid down rules are followed. Research study found that there are continuous checks to ensure controls are working well. The study established a significant relationship between ICS and fraud control. The researcher recommends that the management of these institutions should establish proper mechanisms of promoting qualified and deserving employees, also the institutions should ensure fair remunerations based on qualification, responsibilities and output of employees. The study recommends that the financial institutions establish and manages knowledge or information management system within the institution, so as to enable all parties within the institution to freely access and utilize necessary official information that will enable the employees to embrace and appreciate their roles in enhancing vigilance against fraudsters.